Characterization of the egg masses of wedge sea hare, Dollabella auricularia (Lightfoot, 1786) from Danao-Carmen Cove, Cebu , Philippines - Pepito, Ador Rivera (University of the Philippines Visayas, 2016)
The egg mass locally, known as "lukot" of the wedge sea hare Dolabella auricularia is considered as one of the seafood products in the Visayas region. It is traditionally consumed as raw r an added ingredient to a soup made from fish or shellfish. Although there have been no reported incidence of food poisoning due to the consumption of these egg masses, a preliminary study revealed the potential presence of some toxic substances in the samples. Likewise, no detailed study on the chemical characteristics of these egg masses has been reported. Hence, this study was conducted to determine the toxicity potential and the effect of the post harvest treatment on the chemcial quality of the egg mass. Different post harvest treatments were employed in this study includes acidified, boiled and the combination of the two.No significant differences among all treatments on the lowering of the toxicity potentials of the egg mass were observed. This low toxicity potential could be attributed to the effect of seasonal variation in the sample and its habitat. Different post harvest treatments, on the other hand, reveal different effects on the chemical characteristics of the egg masses. Acidified and the combination of acidified and boiled samples show high protein, carbohydrates and ash content. Boiling of samples resulted to an increase in moisture retention and potassium while acidified samples resulted in high calcium nd potassium. Raw or fresh samples show high total fat, ash, sodium and zinc content. In terms of amino acid profile, the egg masses have six(6) essential, nine (9) non-essential and eight(8) other amino acid components. These results indicate that the egg masses of the wedge sea hare can be considered as a good potential exotic nutritious food commodity from marine environment.